Constructing a STEM Projects Design Framework for Middle School AI Courses: Developing Students’ AI Literacy as Project Goals - Hongwu Yang; Di Zhang; Weitong Guo; Yanshan He (IEEE Access)
In our modern era, it has become essential for citizens to possess artificial intelligence (AI) literacy to navigate an AI-driven society. However, there is a current deficiency in students’ AI literacy. In response to this challenge, this article introduced the AI STEM Project Design Framework (AI-STEM PDF) designed specifically for teaching AI in middle schools. The framework, created in adherence to Activity Theory and the principles of STEM environment design, consists of five layers: subject-object analysis layer, project design layer, learning tool layer, project rules layer, and project goals layer. Following the development of the AI-STEM PDF, AI-STEM projects were devised, and a pre-post experimental design study was conducted with 64 middle school students across two schools. The results revealed significant improvements in students’ AI literacy, thus affirming the value of the AI-STEM framework. Ultimately, the AI-STEM PDF has the potential to enhance the effectiveness of AI courses by providing valuable guidance for their instruction, thereby fostering the development of middle school students’ AI literacy.